Sustainability: The new element for creating competitive advantage - Pires, M. C.; Pereira, L. F.; Crespo de Carvalho, J.; Vinhas da Silva, R.; Simões, A. (Progress in Industrial Ecology, 2024)
Businesses have become more concerned about sustainability, which affects both the business world and our society. Sustainability is now seen as a key driver for future development and innovation, but only for those companies that implement it in their business strategy. With these concerns, the problem statement that this research seeks to answer is 'how to implement sustainability in business strategy'. The research objectives are to identify the main issues related to business sustainability, how sustainability is changing the business world, how companies can implement sustainability in their business strategy and to correlate the empirical evidence with the interviews. To achieve these objectives, data was collected through 101 interviews from the book 101 Voices for Sustainability, for a Responsible Development. The main findings were that companies in Portugal and worldwide are very concerned about sustainability and megatrends, and that Portuguese companies have megatrend opportunities that can be addressed.